Respuesta :
The answer is: [A]:
_________________________________________________
" 4(y – z) = 4(y) + 4(-z) "
_________________________________________________
Note the "distributive property of multiplication" :
_________________________________________________
a(b+c) = ab + ac ; AND:
a(b−c) = ab − ac ;
__________________________________________________
_________________________________________________
" 4(y – z) = 4(y) + 4(-z) "
_________________________________________________
Note the "distributive property of multiplication" :
_________________________________________________
a(b+c) = ab + ac ; AND:
a(b−c) = ab − ac ;
__________________________________________________